2018
DOI: 10.1103/physrevlett.121.103002
|View full text |Cite
|
Sign up to set email alerts
|

Control of H2 Dissociative Ionization in the Nonlinear Regime Using Vacuum Ultraviolet Free-Electron Laser Pulses

Abstract: The role of the nuclear degrees of freedom in nonlinear two-photon single ionization of H_{2} molecules interacting with short and intense vacuum ultraviolet pulses is investigated, both experimentally and theoretically, by selecting single resonant vibronic intermediate neutral states. This high selectivity relies on the narrow bandwidth and tunability of the pulses generated at the FERMI free-electron laser. A sustained enhancement of dissociative ionization, which even exceeds nondissociative ionization, is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 40 publications
1
7
0
1
Order By: Relevance
“…The drawback is that, for the time being, FELs generate longer pulses, although very recent work has already shown that generation of sub‐1‐fs pulses in X‐FELs is already possible . In any case, experimental measurements using FELs have shown that one can control the ratio between dissociative and nondissociative ionization in H 2 , as previously predicted by calculations based on the spectral method . The applications and capabilities of FEL facilities are rapidly expanding, with remarkable progress in carrier phase and light polarization control .…”
Section: Molecular Attosecond Dynamicsmentioning
confidence: 99%
See 1 more Smart Citation
“…The drawback is that, for the time being, FELs generate longer pulses, although very recent work has already shown that generation of sub‐1‐fs pulses in X‐FELs is already possible . In any case, experimental measurements using FELs have shown that one can control the ratio between dissociative and nondissociative ionization in H 2 , as previously predicted by calculations based on the spectral method . The applications and capabilities of FEL facilities are rapidly expanding, with remarkable progress in carrier phase and light polarization control .…”
Section: Molecular Attosecond Dynamicsmentioning
confidence: 99%
“…Experiments are now trying to improve the shot‐to‐shot reproducibility, carrier phase stabilization and detection methods, as well as to increase the pulse intensities in order to retrieve the complete wave packet. In this direction, recent experiments have made use of UV pulses generated in free‐electron laser (FEL) facilities, which are able to produce much higher intensities and thus offer, a priori, an improved noise‐to‐background signal for two‐photon processes. The drawback is that, for the time being, FELs generate longer pulses, although very recent work has already shown that generation of sub‐1‐fs pulses in X‐FELs is already possible .…”
Section: Molecular Attosecond Dynamicsmentioning
confidence: 99%
“…Later this process was used to reveal a doublet structure of the giant resonance in Xe (Mazza et al, 2015b;Chen et al, 2015). Holzmeier et al (2018) employed resonant two-photon spectroscopy of H 2 to investigate nuclear dynamics in the ionization process. Molecular ionization is much more complicated than the atomic case, even for a system as simple as hydrogen, because of the additional nuclear degrees of freedom, especially the vibrational degrees.…”
Section: One-colour Two-photon Ionizationmentioning
confidence: 99%
“…Percobaan telah menunjukkan bahwa ion negatif F− adalah produk dominan dari keterikatan disosiatif elektron (186)(187)(188)(189)(190)(191) . Penampang untuk proses ini adalah antara dua hingga empat lipat lebih besar dari yang untuk penciptaan F−2 dan NF−2 ion Kami menggunakan penampang eksitasi getaran dari Dyatko dan Napartovich, eksitasi disosiatif (192)(193)(194) penampang Rescigno , dan ionisasi eksperimental penampang dari Tarnovsky.…”
Section: Koefesien Disosiatifunclassified